Accounting and accountability challenges: Implementing sustainability in tertiary organisations. (2014) - ,
Abstract : Purpose – This paper aims to investigate the strategy, accounting and accountability interface in sustainability implementation in a large public tertiary education organisation in New Zealand.Design/methodology/approach – The study uses ethnography as an "engaging research" to help explain the real‐life enactment of accounting and accountability in advancing/deterring sustainability initiatives. The study draws upon neo‐institutional theoretical perspectives to help interpret the findings.Findings – Accounting and accountability are powerful conduits for strategy implementation. Successful sustainability strategy implementation requires the embedding of financial accountability within the implementation process.Practical implications – A strong ideological commitment from senior management is required to firmly embed sustainability in the tertiary organisation's belief systems, values and norms to get wider organisational acceptance and institutionalisation. Accounting needs to take a position of centrality within organisations to help facilitate sustainability implementation.Social implications – Government policy needs to incorporate specific concepts of sustainability into the tertiary education strategy and funding framework to make public tertiary organisations accountable for sustainability to the wider society.Originality/value – This study provides unique insights into the sustainability implementation process. It complements existing literature on sustainability accounting and accountability.